2016
DOI: 10.1589/jpts.28.1150
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of knee and ankle joint angles and ground reaction force according to functional differences during single-leg drop landing

Abstract: [Purpose] The purpose of this study was to determine potential predictors of functional instability of the knee and ankle joints during single-leg drop landing based on the prior history of injury. [Subjects and Methods] The subjects were 24 collegiate soccer players without pain or dysfunction. To compare the differences between the stable and unstable sides during single-leg drop landing, 8 motion analysis cameras and a force plate were used. The Cortex 4 software was used for a biomechanical analysis of 3 e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 30 publications
(38 reference statements)
2
7
0
1
Order By: Relevance
“…Muscle pre-activation during the flight phase of landing was used to indicate a continuous build-up of muscle force occurring before the touchdown to (1) form initial stiffness of the contractile component, which enables the use of elastic energy from muscle-tendon structures in conjunction with the muscle contractile property, and (2) provide adequate deceleration of joint flexion during dynamic activities, which may be a mechanism acting to protect the musculoskeletal system from injury (Vladimir et al, 2008). As expected, our findings showed that the significantly decreased pre-activation EMG in UDL led to a stiff landing, with the hip and knee joints showing significantly lower flexion at the touchdown phase, lower changes in the joint angle, and relatively higher leg stiffness, which caused greater impact of ground reaction force compared with ADJ (Kim and Jeon, 2016).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Muscle pre-activation during the flight phase of landing was used to indicate a continuous build-up of muscle force occurring before the touchdown to (1) form initial stiffness of the contractile component, which enables the use of elastic energy from muscle-tendon structures in conjunction with the muscle contractile property, and (2) provide adequate deceleration of joint flexion during dynamic activities, which may be a mechanism acting to protect the musculoskeletal system from injury (Vladimir et al, 2008). As expected, our findings showed that the significantly decreased pre-activation EMG in UDL led to a stiff landing, with the hip and knee joints showing significantly lower flexion at the touchdown phase, lower changes in the joint angle, and relatively higher leg stiffness, which caused greater impact of ground reaction force compared with ADJ (Kim and Jeon, 2016).…”
Section: Discussionsupporting
confidence: 77%
“…In the present study, the landing strategy was the main factor affecting the ground reaction force without considering the test environments. Thus, stiff landings caused a greater ground reaction force than soft landings (Kim and Jeon, 2016). Moreover, soft and stiff landings had relatively large and small amounts of knee flexion, respectively, during the floor contact phase.…”
Section: Discussionmentioning
confidence: 99%
“…Traditionally, lower limb joint kinematics have been evaluated under laboratory settings using camera-based motion capture systems [16][17][18]. However, this method cannot be used to track movements in the field.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 Improved muscle activation can provide stability, thus decreasing the risk for injury to occur during landing. 6,8,[18][19][20][21] There is a relationship between the proximal and distal joints of our lower extremity. 16,17 Following the kinetic linking, ankle invertors, evertors, and GMeds are responsible for movements and stability in the frontal plane of the ankle joint.…”
Section: Introductionmentioning
confidence: 99%